2016
DOI: 10.5762/kais.2016.17.10.261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motive for Major Selection on Major Satisfaction, Campus-life Satisfaction, and Self-directed Learning Ability among Nursing Students

Abstract: This study attempted to survey nursing students' motives for choosing nursing as their major, and to examine how such motives affect their satisfaction with their major, campus-life satisfaction, and self-directed learning ability. This study was conducted as a descriptive survey. Data were collected using a self-report questionnaire during the period from the 1st to 15th of April, 2015, and the questionnaires from 195 nursing students were used in the analysis using Fisher's exact test, t-test, one way ANOVA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The most frequent extrinsic motivation was the perceived ease of getting a job (40.5%), followed by choosing nursing major based on high-school grades (15.5%). Previous studies have shown that more than half of nursing students reportedly selected their major due to external motivation, rather than intrinsic motivation [27], which is in line with the findings of the current study. Another previous study reported that in South Korea the primary reason nursing students chose their major was employability (55%), followed by aptitude (20%); whereas, non-nursing students cited aptitude (48%), and employability (23%) as the most important reasons for their major choice [21].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most frequent extrinsic motivation was the perceived ease of getting a job (40.5%), followed by choosing nursing major based on high-school grades (15.5%). Previous studies have shown that more than half of nursing students reportedly selected their major due to external motivation, rather than intrinsic motivation [27], which is in line with the findings of the current study. Another previous study reported that in South Korea the primary reason nursing students chose their major was employability (55%), followed by aptitude (20%); whereas, non-nursing students cited aptitude (48%), and employability (23%) as the most important reasons for their major choice [21].…”
Section: Discussionsupporting
confidence: 92%
“…The results of a few previous studies have shown that intrinsically motivated nursing students were more likely to be satisfied with their chosen major, university life, and self-directed learning ability than extrinsically motivated students [27], and intrinsic motivation was also shown to reduce test anxiety [28]. There is little research on the relationship between academic motivation and PTG among nursing students, therefore making any direct comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our findings suggest that the influence of a patriarchal cultural background can be overcome by demographic characteristics, motives for MS, and academic achievement. This is also supported by the results of previous studies [ 25 , 26 , 27 ], which showed that motive can affect MS. In these studies, MS was highest in students who voluntarily chose their majors based on suitability and interest.…”
Section: Discussionsupporting
confidence: 90%